Group of Eskimo women around cooking fire, Alaska, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: Kow Kow Pe Chuk Tuk, Too Many Cooks Spoil The Broth. Copyright, F.H. Nowell. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number